Identification of Causes and Effects of Poor Communication in Construction Industry: A Theoretical Review - Yaser Gamil; Ismail Abdul Rahman (Ital Publication, 2017)
Construction industry is characterized in nature as complex, fragmented, dynamic and involves many parties therefore effective communication is essential to overcome these challenges. Many researchers found that the industry faces major challenge to ensure effective and successful communication throughout the lifecycle of the project which therefore resulted to project failure. Poor communication in construction industry had been addressed in previous research studies; however, this paper presents and examines the identification of causes and effects which lead to poor communication. Further investigations on previous literature were conducted to extract the causes and effects which contributed to poor communication in construction industry. Similarity technique was applied to avoid duplications in the identified causes and effect of poor communication. Using the frequency technique, from the 33 causes of poor communication it was found that the most dominant cause is lack of effective communication. Whereas, out of 21 effects from poor communication, it was found that highly repeated effect is time overrun. These findings will serve a good platform for further investigation on the relevancy of causes and effects to the local construction practitioners.